Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

Compétences linguistiques et culturelles des organisations de santé. Analyse critique de la littérature - Aucoin, Léonard (InfoVeille Santé, 2008)

Diverging socioeconomic inequality in life expectancy of Francophones and Anglophones in Montréal, Québec: Tobacco to blame? - Auger, Nathalie; Harper, Sam; Barry, Amadou D. (Journal of Public Health: From Theory to Practice, 2013)
Aim We evaluated the ages and causes of death contributing to life expectancy gaps between economically advantaged and disadvantaged Francophones and Anglophones of Montréal, a Canadian metropolitan centre. Subject and Methods We partitioned the life expectancy gap at birth between socioeconomically disadvantaged and advantaged Francophones and Anglophones of Montréal (Québec) into age and cause of death components for two periods (1989–1993, 2002–2006). Changes in the contributions of causes over time were evaluated. Results Life expectancy was lower for disadvantaged Francophones and Anglophones by 5 years in men and 1.6 years in women compared with advantaged individuals. Over time, the socioeconomic gap widened for Francophones (men 0.3 years, women 2.8 years), due to smaller reductions in mortality from tobacco-related causes (cardiovascular, cancer, respiratory) in disadvantaged than in advantaged Francophones, especially after age ≥65 years (except lung cancer mortality that increased, particularly in disadvantaged women). The socioeconomic gap narrowed, however, for Anglophones (men 1.0 year, women 0.6 years), due to greater reductions in cardiovascular mortality in disadvantaged than advantaged Anglophones. Conclusion Socioeconomic inequalities in life expectancy decreased for Anglophones but increased for Francophones in Montréal due to underlying trends in tobacco-related mortality. Despite strong tobacco control laws in Canada, socioeconomic inequality in tobacco-related mortality is widening for Francophones in Montréal.

Life expectancy gap between the Francophone majority and Anglophone minority of a Canadian population - Auger, Nathalie; Harper, Sam; Barry, Amadou D.; Trempe, Normand; Daniel, Mark (European Journal of Epidemiology, 2012)
Language is an important determinant of health, but analyses of linguistic inequalities in mortality are scant, especially for Canadian linguistic groups with European roots. We evaluated the life expectancy gap between the Francophone majority and Anglophone minority of Québec, Canada, both over time and across major provincial areas. Arriaga’s method was used to estimate the age and cause of death groups contributing to changes in the life expectancy gap at birth between 1989–1993 and 2002–2006, and to evaluate patterns across major provincial areas (metropolitan Montréal, other metropolitan centres, and small cities/rural areas). Life expectancy at birth was greater for Anglophones, but the gap decreased over time by 1.3 years (52% decline) in men and 0.9 years (47% decline) in women, due to relatively sharper reductions in Francophone mortality from several causes, except lung cancer which countered reductions in women. The life expectancy gap in 2002–2006 was widest in other metropolitan centres (men 5.1 years, women 3.2 years), narrowest in small cities/rural areas (men 0.8 years, women 0.7 years), and tobacco-related causes were the main contributors. Only young Anglophones <40 years in small cities/rural areas had mortality higher than Francophones, resulting in a narrower gap in these areas. Differentials in life expectancy favouring Anglophones decreased over time, but varied across areas of Québec. Tobacco-related causes accounted for the majority of the current life expectancy gap.

Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

L’accès aux soins de santé pour les communautés minoritaires de langue officielle : fondements juridiques, initiatives actuelles et perspectives d’avenir - Bélanger, Mauril; Comité permanent des langues officielles (Gouvernement du Canada, Chambre des communes, 2003)

Programme d’accès aux services de santé et aux services sociaux en langue anglaise de la Côte-Nord - Bilodeau, Nancy; Paradis, Pascal; Morin, Sandra (Agence de la santé et des services sociaux de la Côte-Nord, 2011)

Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

La santé en francophonie canadienne : vivre en situation minoritaire influence-t-il la santé ? - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène (Bulletin de l’association des médecins de langue française, 2009)
La littérature suggère l'hypothèse d'une santé différentielle des francophones en situation minoritaire au Canada. L'effet de minorité sur la santé perçue a été mesuré à l'aide des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) de 2001 et 2003. Une analyse de régression logistique multivariée séquentielle montre que les francophones minoritaires – hommes et femmes – sont plus enclins à déclarer une moins bonne santé que les anglophones majoritaires. Contrairement aux femmes, cette disparité chez les hommes demeure significative même lorsque nous ajustons pour certains grands déterminants de la santé. L'étude illustre que l'action des déterminants de santé peut être ainsi modulée par le rapport minoritaire/majoritaire. Les inégalités ainsi révélées appellent à une réflexion sur les politiques d'accès linguistique aux soins de santé.

Health profile of English-speaking minority communities in Quebec [infographic] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)

Profil santé des communautés anglophones minoritaires au Québec [infographie] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H. et Gagnon-Arpin, I. (2009). Profil santé des communautés anglophones minoritaires au Québec [infographie]. Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada (RISF). Santé Canada. fs-code-orig: Bouchard-2009e

La santé en situation linguistique minoritaire - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gilbert, A.; Dubois, L. (Politiques de Santé, 2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H., Gilbert, A. et Dubois, L. (2009). La santé en situation linguistique minoritaire. Politiques de Santé, 4(4), 36-42. https://www.ncbi.nlm.nih.gov/pmc/Article de revue s/PMC2700700/pdf/policy-04-036.pdf fs-code-orig: Bouchard-2009a

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Health profile of English-speaking minority communities in Canada [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)
fs-ref-orig: Bouchard, L., Sampasa-Kanyinga, H., & Mukaneza, A. (2018). Health profile of English-speaking minority communities in Quebec [infographic]. University of Ottawa and Institut du savoir Montfort. fs-code-orig: Bouchard-2018f

Profil santé des communautés anglophones en situation minoritaire au Québec [infographie] - Bouchard, Louise; Sampasa-Kanyinga, hugues; Mukaneza, anne (2018)
fs-ref-orig: Bouchard, L., Sampasa-Kanyinga, H. et Mukaneza, A. (2018). Profil santé des communautés anglophones en situation minoritaire au Québec [infographie]. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2018e

Bilingual health care in Quebec: Public policy, vitality, and acculturation issues - Bourhis, Richard Y. (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Abstract The first part of this chapter offers the Interactive Acculturation Model (IAM), which provides an intergroup approach to minority/majority group relations in multilingual settings. The ethnolinguistic vitality framework is the first element of the IAM as it describes the relative strength and weaknesses of linguistic communities in contact. Four language policies regulating the status of linguistic communities constitute the key second element of the IAM. Third, the acculturation orientations of minority and majority group speakers are described as they interact to yield harmonious, problematic or conflictual intergroup relations. As an application of the IAM, the second part of the chapter analyzes bilingual health care policies for official language minorities in Canada and Quebec. A detailed analysis of bilingual health care institutions serving the English-speaking communities of Quebec closes with a case study of a recent Quebec Government health care law that threatened to undermine the institutional vitality of the Anglophone minority of Quebec. Key words: Interactive Acculturation Model (IAM), English-speaking communities of Quebec, health care policies.
Chapter 14

The vitality of the English-speaking communities of Quebec: From community decline to revival - Bourhis, Richard Y. (Centre d’études ethniques des universités montréalaises, Université de Montréal, 2008)

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)
Chapter: 4

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Programme de contribution pour l'amélioration de l'accès aux services de santé pour les communautés de langue officielle en situation minoritaire. Évaluation formative. - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Suicide mortality gap between Francophones and Anglophones of Quebec, Canada - Burrows, Stephanie; Auger, Nathalie; Tamambang, Lum; Barry, Amadou. D. (Social psychiatry and psychiatric epidemiology, 2013)
Purpose Few studies evaluate language-group differences in suicide mortality. This study assessed the suicide mortality gap between Francophones and Anglophones of Quebec, Canada according to age, sex, method, region and socioeconomic deprivation. Methods Suicide decedents were extracted from the Quebec death file for 1989–2007 (N = 24,465). Age- and sex-specific suicide mortality rates were calculated for four periods (1989–1993, 1994–1998, 1999–2003, 2004–2007) for Francophones and Anglophones aged ≥10 years. Age-standardized rates of suicide by method, region, and level of social and material deprivation were calculated for each sex. Rate ratios and rate differences were estimated. Results Suicide rates for Francophones were two to three times higher than rates for Anglophones, and differences were greatest for adults aged 25–64 years. Francophone males had more than two times the rate of suicide by hanging or firearms than Anglophone males. Francophone females had twice the rate of hanging, poisoning or firearm suicide as Anglophone females, although precision was low. Francophone-Anglophone suicide mortality gaps were higher in urban areas despite lower suicide rates, and varied little across levels of social and material deprivation. Conclusions There was a large suicide mortality gap between Francophones and Anglophones of Quebec; especially, among adults aged 25–64 years.

Quel avenir pour les services sociaux et de santé des communautés anglophones du Québec ? - Carter, Jane (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)
Chapitre 6

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

The principle of minority protection and language rights in Canada: The secession reference’s legacy - Chouinard, Stéphanie (Journal of Parliamentary and Political Law, 2021)

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

L’offre active une culture de respect, une culture d’excellence : dépliant [infographie] - Commissariat aux langues officielles (2019)
fs-ref-orig: Commissariat aux langues officielles. (2019). L’offre active une culture de respect, une culture d’excellence : dépliant [infographie]. fs-code-orig: Commissariat aux langues officielles-2019

L’offre active une culture de respect, une culture d’excellence : guide complet [infographie] - Commissariat aux langues officielles (2017)
fs-ref-orig: Commissariat aux langues officielles. (2017). L’offre active une culture de respect, une culture d’excellence : guide complet. fs-code-orig: Commissariat aux langues officielles-2017.

Une question de respect et de sécurité : l’incidence des situations d’urgence sur les langues officielles - Commissariat aux langues officielles (Gouvernement du Canada, 2020)

Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

English-language Health and Social Services Access in Québec. Comparison 2019-2023 - CROP (Community Health & Social Services Network, 2023)

L’accès en anglais aux services de santé et aux services sociaux au Québec. Version française du rapport comparatif 2023-2019 - CROP (Community Health & Social Services Network, 2024)

Accessibility and active offer: Health care and social services in linguistic minority communities - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe (University of Ottawa Press, 2017)
This edited volume examines language issues within the active offer of health and social services in francophone and anglophone minority communities. Action based, it will help shape the leaders of tomorrow. It is imperative that we train leaders who are able to intervene efficiently with service users and to support a better organization of the workplace. It is especially important to look at the many issues related to postsecondary training and human resources, such as recruiting and keeping these leading professionals. Accessibility and Active Offer thus combines theory and empirical data to help future professionals understand the workplace issues of accessibility and active offer of minority-language services. This English-language adaptation of Accessibilité et offre active features an additional chapter by Richard Bourhis on issues specific to Anglophone communities in Québec.

Identification des communautés anglophones du Québec : approche populationnelle dans le cadre de l’évaluation des disparités de santé associées à l’infarctus du myocarde - Drouin, Catherine; Courteau, Josiane; Orzanco, Maria Gabriela; Leroux, Denis; Vanasse, Alain (Revue d’études des Cantons-de-l’Est, 2011)
Il existe peu de données probantes permettant d’évaluer les disparités en matière de santé entre les groupes linguistiques au Québec. Ce projet propose une méthode de classification des communautés du Québec en fonction de l’appartenance linguistique de la population ainsi que l’association, basée sur le lieu de résidence des patients, des données médico-administratives et de celles du recensement. Ensuite, des comparaisons entre les groupes linguistiques quant aux traitements et au suivi des cas d’infarctus du myocarde, réalisées à l’aide de tests du Khi carré, permettent d’identifier que la principale disparité se manifeste dans les taux de revascularisation.

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Les disparités d'accès aux soins de santé parmi la minorité de langue officielle au Québec - Falconer, James; Quesnel-Vallée, Amélie (Recherches sociographiques, 2014)
Cette étude examine l’effet de l’aptitude en français sur la santé et sur les besoins de soins de santé non satisfaits au Québec, en utilisant un modèle multiple de régression logistique. Nos résultats indiquent que les anglophones unilingues du Québec sont 26 % plus susceptibles que les anglophones bilingues à se déclarer en mauvaise santé. Théoriquement, ce mauvais état de santé devrait mener à une utilisation accrue des soins de santé. Cependant, malgré leur mauvais état de santé, les anglophones unilingues sont 52 % plus susceptibles de déclarer des besoins en soins de santé non satisfaits. Ces disparités dans l’état de santé ainsi que dans l’accès aux soins de santé s’expliquent par l’aptitude à s’exprimer en français. Par ailleurs, ces effets ne sont pas modifiés par l’inclusion de variables potentiellement confondantes telles que les caractéristiques sociodémographiques et socioéconomiques. Les résultats suggèrent que ce sont les politiques visant à réduire les obstacles à l’accès aux soins de santé des populations minoritaires qui pourraient améliorer l’accès aux soins, et, éventuellement, la santé des anglophones unilingues du Québec. Mots-clés : populations minoritaires de langue officielle, anglophones, Québec, utilisation des services de santé, inégalités de santé, accès aux soins de santé

L'intervention du gouvernement fédéral canadien en matière de droits linguistiques dans le secteur de la santé - Farley, Roger; Guillemette, Roger; Rivest, François (2015)

Seeking social services on the Gaspé coast: A narrative analysis of Anglophones’ experiences of access and care [master's thesis, University of Victoria] - Finlayson, S. (University of Victoria, 2017)
This research addresses the concern that Anglophone populations in the predominantly French speaking Gaspé region of eastern Québec are experiencing high rates of social problems such as poverty and unemployment. Anglophones in this region, as in other rural regions of Québec, have identified facing difficulties related to access to social services, an aspect which further complicates existing social problems. Using a narrative methodology and post structural, feminist and intersectional lenses, this research explores the experiences of English speaking service users in accessing and engaging with social services on the Gaspé coast. This study also explores the boundaries and reproduction of linguistic categories and identity and offers insight into resisting dominant discourses pertaining to linguistic difference in Québec, specifically within the context of social services. The results of this research demonstrate that service users’ experiences were characterised by disproportionately negative effects in regards to service access and delivery such as intensified logistical problems and social work practice related weaknesses. The research also concludes that experiences involved multiple, intersecting problems, which were irreducible to the singular dimension of language. The intersections of language and race, language and class, and language and ability were raised as critical concerns in terms of access to social services on the Gaspé coast. Finally, the encounters between Anglophones and Francophones in the context of health and social services in the region were found to be entangled and inseparable from the historical and ongoing political struggles over language on this territory.

Le statut socioéconomique des anglophones du Québec : ceux qui sont partis et ceux qui sont restés - Floch, William; Pocock, Joanne (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)

Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa] - Gagnon-Arpin, Isabelle (University of Ottawa, 2011)
fs-ref-orig: Gagnon-Arpin, I. (2011). Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa]. uO Research. http://dx.doi.org/10.20381/ruor-4657 fs-code-orig: Gagnon-Arpin-2011c

Accès et utilisation des services de santé en langue minoritaire - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (La vie dans une langue officielle minoritaire au Canada, 2014)
fs-ref-orig: Gagnon-Arpin, I., Bouchard, L., Leis, A. et Bélanger, M. (2014). Accès et utilisation des services de santé en langue minoritaire. Dans R. Landry (dir.), La vie dans une langue officielle minoritaire au Canada (p. 195-221). Presses de l’Université Laval. fs-code-orig: Gagnon-Arpin-2014b

Access and use of health care services in the minority language - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (Life within an official language minority in Canada, 2014)
fs-ref-orig: Gagnon-Arpin, I., Bouchard, L., Leis, A., & Bélanger, M. (2014). Access and use of health care services in the minority language. In R. Landry (Ed.), Life within an official language minority in Canada (pp. 177-198). Canadian institute for research on Linguistic Minorities. fs-code-orig: Gagnon-Arpin-2014a

Investir dans notre avenir 2018-2023. Plan d'action pour les langues officielles - Gouvernement du Canada (Plan d'action pour les langues officielles, 2018)
fs-ref-orig: Gouvernement du Canada. (2018). Investir dans notre avenir 2018-2023. Plan d'action pour les langues officielles. fs-code-orig: Gouvernement du Canada-2018a

Investing in our future 2018-2023. Action plan for official languages - Government of Canada (Action plan for official languages, 2018)
fs-ref-orig: Government of Canada. (2018). Investing in our future 2018-2023. Action plan for official languages. fs-code-orig: Government of Canada-2018b

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Portrait des services bilingues offerts au sein des hôpitaux canadiens. Rapport - Guignard Noël, Josée; LeBlanc, J.; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Étude de référence sur les services bilingues au sein des établissements de santé canadiens - Guignard Noël, Josée; LeBlanc, Joannie; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2016)

Frontières linguistiques et culturelles : le cas de l’accessibilité aux services de santé et de services sociaux pour la population anglophone de la région de Québec - Hanrahan, Louis; Cloutier, Annabelle; Walling, Richard (Cahiers de l’ÉDIQ, 2016)

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance
The standard can be bought from this web page.

Client and family information sheet: Access to health and social services in Official Languages Standard - Health Standards Organization (2018)
The CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages Standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. This information sheet explains what should be expected from health and social service organizations applying this standard.

Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais.
Ce document qui décrit la norme créé en 2018 n'est plus disponible. La norme a été révisée en 2022 et c'est cette révision de 2022 qui peut être acheté sur la page web suivante: https://healthstandards.org/fr/standard/acces-aux-services-de-sante-et-aux-services-sociaux-dans-les-langues-officielles-confirmation/

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité
La norme peut être achetée à partir de cette page web.

Feuillet d'information pour les usagers et les familles : norme sur l'Accès aux services de santé et aux services sociaux dans les langues officielles - Health Standards Organization / Organisation de normes en santé (2018)
La norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Ce feuillet d'information explique ce à quoi les usagers peuvent s'attendre des organismes de santé et de services sociaux qui appliquent cette norme.

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Amy. T.; Ménard, Alixe; Scott, Mary (Université d'Ottawa et Institut de recherche Bruyère, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A. et Scott, M. (2022). Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux. Université d'Ottawa et Institut de recherche Bruyère. fs-code-orig: Hsu-2022a

Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Hsu, Amy; Ménard, Alixe; Scott, Mary (Bruyère Research Institut, 2022)
fs-ref-orig: Hsu, A. T., Ménard, A., & Scott, M. (2022). Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Bruyère Research Institut. fs-code-orig: Hsu-2022b

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Identifying second language speech tasks and ability levels for successful nurse oral interaction with patients in a linguistic minority setting: An instrument development project - Isaacs, Talia; Laurier, Michel. D.; Turner, Carolyn. E.; Segalowitz, Norman (Health communication, 2011)
One of the most demanding situations for members of linguistic minorities is a conversation between a health professional and a patient, a situation that frequently arises for linguistic minority groups in North America, Europe, and elsewhere. The present study reports on the construction of an oral interaction scale for nurses serving linguistic minorities in their second language (L2). A mixed methods approach was used to identify and validate a set of speech activities relating to nurse interactions with patients and to derive the L2 ability required to carry out those tasks. The research included an extensive literature review, the development of an initial list of speech tasks, and validation of this list with a nurse focus group. The retained speech tasks were then developed into a questionnaire and administered to 133 Quebec nurses who assessed each speech task for difficulty in an L2 context. Results were submitted to Rasch analysis and calibrated with reference to the Canadian Language Benchmarks, and the constructs underlying the speech tasks were identified through exploratory and confirmatory factor analyses. Results showed that speech tasks dealing with emotional aspects of caregiving and conveying health-specific information were reported as being the most demanding in terms of L2 ability, and the most strongly associated with L2 ability required for nurse–patient interactions. Implications are discussed with respect to the development and use of assessment instruments to facilitate L2 workplace training for health care professionals.

Do you speak English? Traitement sociopolitique de l’accessibilité aux services en santé mentale pour les anglophones du Québec - Kirouac, Laurie; Perreault, Isabelle (Minorités linguistiques et société, 2018)
À la fin des années 1970, le Québec se dote de la Charte de la langue française (Loi 101), qui modifie l’encadrement de la question de la langue de prestation des services de santé et de services sociaux. Parallèlement, de nombreux rapports, comités d’étude et politiques modifient en profondeur les pratiques institutionnelles et communautaires à l’endroit des personnes aux prises avec des problèmes de santé mentale. Depuis ce contexte de grandes transformations, où certaines réponses politiques ont été apportées aux préoccupations linguistiques, qu’en est-il de l’accès aux soins de santé mentale pour les anglophones du Québec ? Nous proposons de retracer dans ses grandes lignes l’évolution du traitement sociopolitique qui a été fait de la question de l’accessibilité des services en santé mentale pour les personnes anglophones en accordant une attention particulière à la situation montréalaise. Mots-clés : Québec, anglophones, santé mentale, minorité linguistique, services de santé

Modèle de mobilisation communautaire pour l’amélioration de la santé et de la vitalité des communautés d’expression anglaise au Québec - Kueber, Russell; Richardson, Mary (Réseau communautaire de santé et des services sociaux et Institut national de santé publique du Québec, 2019)

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistics Canada, 2009)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

Autodétermination du comportement langagier en milieu minoritaire : un modèle conceptuel - Lagacé, Josée; Lefebvre, Pascal (Francophonies d’Amérique, 2005)

Autonomie culturelle, cultures sociétales et vitalité des communautés de langue officielle en situation minoritaire au Canada - Landry, Rodrigue (Minorités linguistiques et société, 2012)
Partant d’un modèle macroscopique des facteurs associés à la vitalité d’une minorité linguistique en situation intergroupe, cet article présente cinq principes expliquant comment les structures sociales s’imposent sur les vécus langagiers des membres de la minorité. Ce même modèle montre comment tant les individus que la collectivité peuvent exercer leur autonomie langagière pour contrer ce déterminisme social. Le modèle de l’autonomie culturelle est explicité et appliqué aux communautés de langue officielle en situation minoritaire (CLOSM) dans le but de faire valoir leur besoin d’autonomie institutionnelle pour assurer leur vitalité au Canada. La reconnaissance du droit à l’autonomie culturelle pourrait être un mode de légitimation des droits propres à ces communautés. Les CLOSM sont décrites comme des prolongements des deux cultures sociétales qui constituent le fondement de la dualité linguistique canadienne. Mots-clés : autonomie culturelle, culture sociétale, vitalité linguistique, droits linguistiques, minorités linguistiques

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

La bilinguisation des services de santé et des services sociaux du Québec - Lefebvre, Mathilde (Institut de recherche en économie contemporaine, 2014)

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)
fs-ref-orig: Léger. (2020). Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final. Santé Canada. fs-code-orig: Léger-2020

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.
fs-ref-orig: Leis, A. et Bouchard,

English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistics Canada, 2017)
fs-ref-orig: Lepage, J.-F. (2017). English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011). Statistics Canada. fs-code-orig: Lepage-2017b

Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistique Canada, 2017)
fs-ref-orig: Lepage, J.-F. (2017). Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011). Statistique Canada. fs-code-orig: Lepage-2017a

Professionnels de la santé et minorités de langue officielle au Canada, 2001 et 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistique Canada, 2017)

La situation socioéconomique des anglophones du Québec - Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2012)
fs-ref-orig: Lussier, M.-H. (2012). La situation socioéconomique des anglophones du Québec. Institut national de santé publique du Québec. fs-code-orig: Lussier-2012a

The socioeconomics status of Anglophones in Québec - Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2012)
fs-ref-orig: Lussier, M.-H. (2012). The socioeconomics status of Anglophones in Québec. Institut national de santé publique du Québec. fs-code-orig: Lussier-2012b

Lifestyle habits and health indicators of Québec Anglophones - Lussier, Marie-Hélène; Trempe, Normand (Institut national de santé publique du Québec, 2013)
fs-ref-orig: Lussier, M.-H., & Trempe, N. (2013). Lifestyle habits and health indicators of Québec Anglophones. Institut national de santé publique du Québec. fs-code-orig: Lussier-2013b

Quelques habitudes de vie et indicateurs de santé des anglophones du Québec - Lussier, Marie-Hélène; Trempe, Normand (Institut national de santé publique du Québec, 2013)
fs-ref-orig: Lussier, M.-H. et Trempe, N. (2013). Quelques habitudes de vie et indicateurs de santé des anglophones du Québec. Institut national de santé publique du Québec. fs-code-orig: Lussier-2013a

À l’intersection des définitions de langues : portrait des communautés linguistiques au Québec et dans les réseaux territoriaux de services en 2016. La langue, déterminant de l'état de santé et de la qualité des services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

At the intersection of language definitions: A portrait of linguistic communities in Québec and its territorial service networks in 2016. Language as determinant of health and quality of services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan - Ménard, Alixe; Scott, Mary; Hsu, Amy T. (2022)
fs-ref-orig: Ménard, A., Scott, M. et Hsu, A. T. (2022). Comprendre l'expérience des soins de longue durée des minorités de langue officielle au Canada : une analyse de l'environnement | Understanding the long-term care experience of official language minorities in Canada: An environmental scan. Institut de recherche Bruyère. fs-code-orig: Ménard-2022

Guide pour l’élaboration du programme d’accès aux services de santé et aux services sociaux en langue anglaise - Ministère de la santé et des services sociaux (2018)

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, R., Brenda; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

« Bâtir sur les fondations - améliorer les résultats pour la santé et accroître la vitalité des communautés anglophones du Québec ». Rapport présenté au ministre fédéral de la santé - Nouvet, Marcel; Maldoff, Eric (Comité consultatif des communautés anglophones en situation minoritaire, 2007)

“Building on the foundations, working toward better health outcomes and improved vitality of Quebec's English-speaking communities”. Report to the Federal Minister of Health - Nouvet, Marcel; Maldoff, Eric (Consultative Commitee for English-Speaking Minority Communities, 2007)

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)
fs-ref-orig: Official Language Community Development Bureau. (2007). Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. Health Canada. fs-code-orig: Official Language Community Development Bureau-2007

Adaptation linguistique des soins et des services de santé : enjeux et stratégies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)
fs-ref-orig: Ouimet, A.-M., Trempe, N., Vissandjée, B. et Hemlin, I. (2013). Adaptation linguistique des soins et des services de santé : enjeux et stratégies. La langue, déterminant de l'état de santé et de la qualité des services. Institut national de santé publique du Québec. fs-code-orig: Ouimet-2013a

Language adaptation in health care and health services: Issues and strategies - Ouimet, Anne-Marie; Trempe, Normand; Vissandjée, Bilkis; Hemlin, Isabelle (Institut national de santé publique du Québec, 2013)
fs-ref-orig: Ouimet, A.-M., Trempe, N., Vissandjée, B., & Hemlin, I. (2013). Language adaptation in health care and health services: Issues and strategies. Language as a determinant of health status and service quality. Institut national de santé publique du Québec. fs-code-orig: Ouimet-2013b

Connaissance et utilisation de la langue officielle minoritaire au travail par les travailleurs de la santé, 2001 à 2016 - Paez Silva, Alejandro. A.; Cornelissen, Louis (Statistique Canada, 2021)

Knowledge and use of the Official Minority Language at work by healthcare workers, 2001 to 2016 - Paez Silva, Alejandro. A.; Cornelissen, Louis (Statistics Canada, 2021)

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Le présent rapport et l’Enquête sur la population de langue officielle en situation minoritaire de 2022 ont bénéficié du soutien financier et de la collaboration soutenue du ministère du Patrimoine canadien. Cette étude a pu être réalisée grâce au travail de longue haleine de plusieurs équipes et personnes qui se sont relayées au fil des ans pour planifier, concevoir, préparer, tester, réaliser, assurer la qualité des données, documenter, analyser et diffuser cette enquête d’envergure. Les auteurs tiennent à remercier toutes les personnes qui ont participé à ce processus, en particulier, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑ Hélène Toupin, Danielle Léger et Catherine Dufour. Plusieurs autres membres du personnel actuel ou passé de Statistique Canada ont contribué de manière importante à cette enquête au fil du temps, dont Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean‑Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu et Dominique Pérusse, de même que les équipes internes des activités de collecte et de traitement des données. Pour leur soutien, leurs conseils et leur aide à la production du rapport, merci à Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini et Pierre‑France Bondesen‑David. Soulignons également l’expertise et l’orientation fournies par les réviseurs ainsi que les membres du comité de direction et les membres du comité scientifique de l’enquête.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
This report and the 2022 Survey on the Official Language Minority Population received funding and ongoing support from the Department of Canadian Heritage. This study was made possible thanks to the tireless efforts of many different teams and individuals who, over the years, contributed to planning, designing, preparing, testing, conducting, ensuring data quality, documenting, analyzing and publishing this major survey. The authors would like to thank each and every one of them, especially, Marie Desnoyers, Éric Caron Malenfant, Daniel Pereira, Claude Girard, Marie‑Hélène Toupin, Danielle Léger and Catherine Dufour. Many other current or former Statistics Canada staff members have made, over the years, important contributions to this survey including Siramane Coulibaly, Catherine Frigon, Julien Acaffou, Paul Brisson, Sara Tello, Jean Pierre Corbeil, Émilie Lavoie, Deniz Do, Jean‑François Nault, Guylaine Dubreuil, Isabelle Lévesque, Daphné Allard Gervais, Geneviève Caron, Geanina Popescu and Dominique Pérusse, as well as the in‑house data collection and processing teams. For their support, advice and help in producing the report, thanks to Laurent Martel, Daphne Fernandes, Juliane Oliveira Pisani Martini and Pierre‑France Bondesen‑David. We would also like to acknowledge the expertise and guidance of the editors, as well as the members of the Interdepartmental Steering Committee and the survey Scientific Committee.

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Demographic Profile of the English-Speaking Communities - Pocock, Joanne (2018)
fs-ref-orig: Pocock, J. (2018, 1er mars). Demographic Profiles of the English-Speaking Communities (a series of report by sanitary region). fs-code-orig: Pocock-2018b

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Quebec’s English-speaking community and the partnership approach of its networks in health - Pocock, Joanne (Linguistic Minorities and Society, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted. Keywords: official language minority communities, intersectoral partnerships, access to public health care, language policy, community-based participatory evaluation (CBPE)

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
fs-ref-orig: Puchala, C., Leis, A., Lim, H., & Tempier, R. (2013). Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? Canadian Journal of Public Health, 104(1), 5‑11. https://www.ncbi.nlm.nih.gov/pmc/Articles/PMC6973939/pdf/41997_2013_Article_1040605.pdf fs-code-orig: Puchala-2013

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

The network’s approaches for the maintenance and creation of primary health services in English for the Quebec City region - Sanderson, Duncan; Grégoire, Louise; Reinharz, Daniel (Agence de la santé et des services sociaux de la Capitale-Nationale & Direction régionale de santé publique, 2006)
fs-ref-orig: Sanderson, D., Grégoire, L., & Reinharz, D. (2006). The network’s approaches for the maintenance and creation of primary health services in English for the Quebec City region. Agence de la santé et des services sociaux de la Capitale-Nationale & Direction régionale de santé publique. fs-code-orig: Sanderson-2006

Pratique # 15 : Le volet « santé et services sociaux » de l’Association des Townshippers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Directory of innovative practices in health and social services in official language minority contexts - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann; Dagnogo, Djenaba Sarah; Michel, Jean Nephetaly

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

French and English among Healthcare Workers in Quebec, 2021 (Infographic) - Statistics Canada (2025)

Table : 15-10-0041-01 Frequency of health care or services obtained in the minority official language, by age group and gender, for adults in the official language minority population - Statistics Canada (Gouvernement du Canada, 2025)
Health services or care in the minority official language by age group and gender, Canada, among adults in the minority official language population who considered it important to obtain health services or care in the minority official language, 2022. Possibility to conduct more specific searches for Quebec, Canada outside Quebec, certain provinces, or certain regions.

English and french among healthcare workers in Quebec, 2001 to 2016 [infographic] - Statistique Canada (2021)

Le français et l’anglais chez les travailleurs de la santé au Québec, 2001 à 2016 [infographie] - Statistique Canada (2021)

Le français et l'anglais chez les travailleurs et travailleuses de la santé au Québec - 2021 (infographie) - Statistique Canada (2025)

Culture, language and self- assesments of future health: Anglophones and Francophones in Quebec’s Eastern Townships - Stout, Dale; Charpentier, Claude; Chiasson, Myriam; Filion, Emmalie (Journal of Eastern Townships Studies, 2009)
This study examines subjective ratings of health (SRH) by Francophones and Anglophones living in the Eastern Townships. Global self-ratings of health are regarded as sensitive predictors of future health states, mortality, functional decline and disability, and utilization of the health-care system. Yet despite their pragmatic value, SRH are poorly understood. Along with a spontaneous monitoring of present health states, culture and language are listed as determinants of SRH. Few studies exist, however, that clearly delineate the direction and degree of effect that culture and language have on SRH. Adopting a temporal assessment of SRH, we asked 358 Anglophones (N=176) and Francophones (N=171) from the Eastern Townships, aged 18 to 95, to rate their health in the past, present, and future. To isolate culture and language effects we also asked participants to rate their future health if they “remained in Quebec”. Results revealed a significant interaction between age and temporal ratings of health (SRH). Turning to the effects of location (unspecified or “in Quebec”) on future health ratings, there was a significant interaction with language. Post hoc tests revealed no significant differences in Francophones’ future health ratings (unspecified or “in Quebec”) but a significant ratings drop was noted for Anglophones if they “remained in Quebec”. After controlling for bilingualism, this interaction remained statistically significant.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.

Pour des services de santé culturellement et linguistiquement adaptés - Tremblay, Suzanne (Société Santé en français et Société Santé et Mieux-être en français du Nouveau-Brunswick, 2011)
Ce document fait rapport des études : Les normes de compétences culturelles et linguistiques en santé : étude exploratoire sur les normes américaines et Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien.

Assessment of validity for the “language spoken at home” variable in Québec death records: Summary. Language, determinant of health status and of services' quality - Trempe, Normand; Boivin, Marie-Claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

La validité de la variable « Langue d’usage à la maison » du Fichier des décès du Québec : synthèse. La langue, déterminant de l'état de santé et de la qualité des services - Trempe, Normand; Boivin, marie-claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

Avoidable mortality of the two main linguistic communities in Québec. Language as a determinant of health status and service quality - Trempe, Normand; Diogo Barry, Amadou D.; Lussier, Marie-Hélène.; Lo, Ernest (Institut national de santé publique du Québec, 2013)
fs-ref-orig: Trempe, N., Diogo Barry, A., Lussier, M.-H., & Lo, E. (2013). Avoidable mortality of the two main linguistic communities in Québec. Language as a determinant of health status and service quality. Institut national de santé publique du Québec. fs-code-orig: Trempe-2013b

La mortalité évitable des deux principales communautés linguistiques du Québec. La langue, déterminant de l'état de santé et la qualité des services - Trempe, Normand; Diogo Barry, Amadou; Lussier, Marie-Hélène; Lo, Ernest (Institut national de santé publique du Québec, 2013)
fs-ref-orig: Trempe, N., Diogo Barry, A., Lussier, M.-H. et Lo, E. (2013). La mortalité évitable des deux principales communautés linguistiques du Québec. La langue, déterminant de l'état de santé et la qualité des services. Institut national de santé publique du Québec. fs-code-orig: Trempe-2013a

Knowledge and use of the English language by healthcare and social services professionals in Québec - Trempe, Normand; Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2011)

La connaissance et l'utilisation de la langue anglaise par les professionnels de la santé et des services sociaux au Québec - Trempe, Normand; Lussier, marie-Hélène (Institut national de santé publique du Québec, 2011)

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action - Vézina, Sylvain; Doiron Robichaud, Johannie (Bureau d’appui aux communautés de langue officielle de Santé Canada, 2011)
fs-ref-orig: Vézina, S. et Doiron Robichaud, J. (2011). Vers une démarche concertée pour le renforcement de la recherche sur les langues officielles dans le secteur de la santé : bilan et pistes d’action. Bureau d’appui aux communautés de langue officielle de Santé Canada. http://docplayer.fr/123792385-Vers-une-demarche-concertee-pour-le-renforcement-de-la-recherche-sur-les-langues-officielles-dans-le-secteur-de-la-sante-bilan-et-pistes-d-action.html fs-code-orig: Vézina-2011

Do nurses use discourse markers differently when using their second language as opposed to their first while interviewing patients? - Yeji, Han; Segalowitz, Norman; Khalil, Laura; Kehayia, Eva; Turner, Carolyn; Gatbonton, Elisabeth (The Canadian Modern Language Review, 2020)
Les auteurs se demandent si l’utilisation de marqueurs discursifs change, dans les interactions des infirmières avec les patients, en fonction de l’usage qu’elles font de leur langue maternelle (L1) ou de leur langue seconde (L2). Les marqueurs sont analysés à titre de marqueurs de maintien du tour de parole, indiquant la « prise en compte » et de marqueurs de transition dans le discours, indiquant un changement de sujet ou de locuteur dans la conversation. Ces deux catégories de marqueurs diffèrent sur le plan du degré de gestion du discours et du contrôle interactionnel. Seize infirmières mènent auprès d’un patient de L1 anglaise et d’un patient de L1 française un entretien visant l’évaluation de la douleur, entretien dans lequel les infirmières utilisent leur propre L1 dans un cas et leur propre L2, moins bien maîtrisée, dans l’autre. Les résultats de l’étude ne permettent pas de confirmer la première hypothèse, selon laquelle les infirmières devraient normalement utiliser les marqueurs discursifs plus fréquemment en L1 qu’en L2. Ils confirment toutefois la seconde hypothèse, selon laquelle les infirmières devraient utiliser les marqueurs de changement de sujet moins fréquemment en L2 qu’en L1, comparativement à leur usage (de base) des marqueurs de maintien du tour de parole. Les constatations des auteurs, en particulier l’attestation de la seconde hypothèse, pourraient avoir des répercussions sur le développement de la formation en L2 des professionnels de la santé.